2001
DOI: 10.2169/internalmedicine.40.1222
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Fibrous Histiocytoma of the Heart: Case Report and Review of 46 Cases in the Literature.

Abstract: A rare case of cardiac malignant fibrous histiocytoma (MFH)is reported. A 55-year-old womancomplained of palpitation due to atrial fibrillation. Echocardiography, magnetic resonance imaging, and angiography demonstrated a tumor arising from the posterior wall of the left atrium. At surgery, the tumor was almost entirely resected and histologically defined as MFH.Neither chemotherapy nor irradiation was administered. Echocardiography revealed a local recurrence two months after the surgery and the patient died … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…As seen by UCG, a nonseptal origin, multiple attachment sites, and infiltration of the mitral valve or atrial wall (or both) were indicative of malignancy. 3,5 In our case, two attachments were observed by preoperative UCG, suggesting the malignant potential of these tumors. Therefore, thorough evaluation of distal metastasis by CT was performed preoperatively.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…As seen by UCG, a nonseptal origin, multiple attachment sites, and infiltration of the mitral valve or atrial wall (or both) were indicative of malignancy. 3,5 In our case, two attachments were observed by preoperative UCG, suggesting the malignant potential of these tumors. Therefore, thorough evaluation of distal metastasis by CT was performed preoperatively.…”
Section: Discussionsupporting
confidence: 47%
“…1 The first case of cardiac MFH was reported by Shah et al 2 in 1978; and 47 cases have since been reported in the literature. 3,4 According to a thorough analysis of the reported cardiac MFH cases by Okamoto et al, the patients' ages ranged from 17 to 77 years, with 62% of the patients female. The most common location of the MFH was the The patient was discharged 15 days after the operation in good condition, and UCG was repeated every 2-3 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one review of 47 cases, dyspnea was the most common presenting complaint (74%) followed by heart palpitations or chest discomfort (40%) [10]. Our case is unique in that the local tumor in the right ventricle remained relatively small while the lung parenchyma was almost entirely invaded by tumor emboli.…”
Section: Discussionmentioning
confidence: 74%
“…Surgical resection with clear margins is the treatment of choice for localized tumors. In addition, surgical resection is necessary to ameliorate symptoms and to obtain a histologic diagnosis despite a high incidence of local recurrence and distant metastasis [10]. Due to the aggressive nature of this tumor, the average survival time is less than one year [13].…”
Section: Discussionmentioning
confidence: 99%